Analysis of codon usage bias and evolution in the chloroplast genome of Mesona chinensis Benth - Tang, Danfeng; Wei, Fan; Cai, Zhongquan; Wei, Yanyan; Khan, Aziz; Miao, Jianhua; Wei, Kunhua (Development Genes and Evolution, 2021)
Mesona chinensis Benth (MCB) is one of the main economic crops in tropical and subtropical areas. To understand the codon usage bias (CUB) in M. chinensis Benth, chloroplast genome is essential to study its genetic law, molecular phylogenetic relationships, and exogenous gene expression. Results showed that the GC content of 53 CDS sequences was 37.95%, and GC1, GC2, and GC3 content were 46.02%, 38.26%, and 29.85%, respectively. The general GC content order was GC1>GC2>GC3. Moreover, the majority of genes had an effective number of codon (ENC) value greater than 40, except ndhE , rps8 , and rps18 . Correlation analysis results revealed that the GC content was significantly correlated with GC1, GC2, GC3, and ENC. Neutrality plot analysis, ENC-plot analysis, and PR2-plot analysis presented that the CUB of M. chinensis Benth chloroplast genome was mainly affected by mutation and selection. In addition, GGG, GCA, and TCC were found to be the optimal codons. Furthermore, results of cluster analysis and evolutionary tree showed that M. chinensis Benth was closely related to Ocimum basilicum , indicating that there was a certain correlation between the CUB of the chloroplast gene and the genetic relationship of plant species. Overall, the study on the CUB of chloroplast genome laid a basis for genetic modification and phylogenetic research of M. chinensis Benth chloroplast genome.